Left ventricular untwist in healthy children and adolescents born full-term - E. N. Pavlyukova; M. V. Kolosova; A. I. Unasheva; R. S. Karpov (Бюллетень сибирской медицины)
The aim of the study is to assess the left ventricle (LV) untwist in healthy children and adolescents born fullterm.Materials and methods. The analysis was carried out in 108 healthy children aged 2 months to 18 years, born full-term. LV untwist is assessed using Speckle Tracking Imaging at the basal and apical level.Results. Four types of LV untwist were identified in children and adolescents. We did not find relation between LV untwist and age, nor with LV index spherical in systole and diastole, LV myocardial mass. The relationship between LV untwisting and LV rotation in systole at basal and apical segments was revealed.Conclusion. The described features of LV loosening are apparently associated with processes of postnatal growth and maturation of heart tissues in children and adolescents.